2023
DOI: 10.1021/acs.jafc.2c08637
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin Ameliorates Nonalcoholic Fatty Liver Disease by Regulating Gut Microbiota and Myristoleic Acid Metabolism

Abstract: Disturbance of the gut microbiota plays a critical role in the development of nonalcoholic fatty liver disease (NAFLD). Increasing evidence supports that natural products may serve as prebiotics to regulate the gut microbiota in the treatment of NAFLD. In the present study, the effect of nobiletin, a naturally occurring polymethoxyflavone, on NAFLD was evaluated, and metabolomics, 16S rRNA gene sequencing, and transcriptomics analysis were performed to determine the underlying mechanism of nobiletin, and the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…Gut dysbiosis was linked to obesity and obesity-related metabolic diseases in humans . An increasing number of experimental and clinical studies have proved that the modulation of gut microbiota is a novel strategy in preventive and therapeutic approaches for MS-related diseases. , To date, several studies have demonstrated that gut microbiota was a potential target for PMFs to ameliorate NAFLD, diabetes, and other MS-related diseases. ,, Among these, Zeng et al confirmed that PMF-rich extracts attenuated MS by targeting and restoring gut microbiota through fecal microbiota transplant and antibiotic treatment experiments . Here, we found that HMF obviously changed the gut microbiota composition at the genus and species levels in HFD-fed mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gut dysbiosis was linked to obesity and obesity-related metabolic diseases in humans . An increasing number of experimental and clinical studies have proved that the modulation of gut microbiota is a novel strategy in preventive and therapeutic approaches for MS-related diseases. , To date, several studies have demonstrated that gut microbiota was a potential target for PMFs to ameliorate NAFLD, diabetes, and other MS-related diseases. ,, Among these, Zeng et al confirmed that PMF-rich extracts attenuated MS by targeting and restoring gut microbiota through fecal microbiota transplant and antibiotic treatment experiments . Here, we found that HMF obviously changed the gut microbiota composition at the genus and species levels in HFD-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that gut microbiota interacts with the host by means of metabolites . Gut microbiota-derived metabolites, particularly bile acids and short-chain fatty acids (SCFAs), have been demonstrated to play a pivotal role in regulating the host’s glucose and lipid metabolism and inflammation. , Many phytochemicals have been demonstrated to prevent and treat MS-related diseases by modulating gut microbiota and microbial metabolites. Li et al found that theabrownin inhibited obesity and NAFLD via modulating the serotonin level and the composition and metabolic function of gut microbiota . Thus, the modulation of gut microbiota and its relevant metabolites might be a novel treatment target for MS-related diseases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple researches have reported the positive effects of NOB on NAFLD. For instance, NOB exerts an antisteatotic effect on the liver by regulating the expression of adiponectin receptor 1 and NADPH oxidase subunit gp91 phox restoring aberrant hepatic circadian rhythm, enhancing lipophagy, as well as targeting gut microbiota and myristoleic acid metabolism . Moreover, our previous study also revealed that NOB mitigates the typical symptoms of NAFLD mice modeled by HFD through reducing the levels of hepatic lipids and serum pro-inflammatory cytokines .…”
Section: Introductionmentioning
confidence: 90%
“…18 Nobiletin, a natural polymethoxy avonoid derived from citrus peels, has been widely reported for its benecial effects including anti-hyperglycemia, antidiabetic, anti-tumor, anti-inammatory, hepatic-protective functions, as well as for its improvement of mitochondrial function and memory loss. [19][20][21][22] Additional, in a rat model of hyperuricemia, orally dosed amorphous solid dispersion of nobiletin showed an improved hypouricemic effect by a 16% reduction in the plasma uric acid level compared with orally administered crystalline nobiletin. 23 Although research into the synthesis and structural modication of myricetin and nobiletin has been extensively carried out, little information has been available on the synthesis of hybrid compounds consisting of myricetin and nobiletin.…”
Section: Introductionmentioning
confidence: 99%